Peran guru dalam pembelajaran pembentukan akhlak mulia terhadap peserta didik - Sasa Alfianti; Nur Khasanah (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
Islamic education plays a crucial role in shaping students' behavior and conduct so that they become faithful, knowledgeable, and have good character. One of the main objectives of education is to build noble moral character. Teachers play a central role by conducting effective learning based on exemplary values. This study was conducted using a qualitative literature review method to analyze the role of teachers in developing noble character and the strategies that can be applied to achieve this goal. The findings show that teachers who act as role models and effectively apply character education strategies can encourage students to internalize positive behavior and build good character. Therefore, improving teachers' competence and awareness of their main role is essential in shaping a generation that is faithful, knowledgeable, and has noble character. The results of this study show that teachers make an important contribution to the development of character education in schools and affirm the strategic role of teachers as agents of change in shaping a superior generation.